Bat E-Commerce: Insights Into the Extent and Potential Implications of This Dark Trade - Chaber, Anne-Lise; Amstrong, Kyle N.; Wiantoro, Sigit; Xerri, Vanessa; Caraguel, Charles; Boardman, Wayne S. J.; Nielsen, Torben D. (Frontiers in Veterinary Science, 2021)
Little is known about the global bat souvenir trade despite previous research efforts into bat harvest for bushmeat. We screened eBay listings of bats in Australia, Canada, Italy, Switzerland, United Kingdom and USA to assess the nature and extent of the online offers. A total of 237 listings were retrieved in between the 11th and 25th of May 2020 with a median price per item of US$38.50 (range: US$8.50-2,500.00). Items on offer were mostly taxidermy (61.2%) or skull (21.1%) specimens. Overall, 32 different species of bat were advertised, most of which (n=28) are listed as ‘Least Concern’ on the International Union for Conservation of Nature (IUCN) Red List. One species (Nycteris javanica) is classified as ‘Vulnerable’ and one (Eidolon helvum) as ‘Near Threatened’. Pteropus spp specimens were the most expensive specimens on offer and the conservations status of these species may range from ‘Critically Endangered’ to ‘Data Deficient’ by IUCN and the entire genus is listed in the Appendix II by the Convention on the International Trade in Endangered Species of Wild Fauna and Flora (CITES). However, the exact species concerned, and their respective conservation status, could not be confirmed based on the listings’ photos. The sourcing of bat was restricted to mostly South-East Asian countries (a third of items sourced from Indonesia) and to two African countries. Our survey revealed that the online offer of bat products is diverse, abundant and facilitated by worldwide sellers although most offered bats species are from South-East Asia. With a few exceptions, the species on offer were of little present conservation concern, however, many unknowns remain on the potential animal welfare, biosecurity, legal implications and most importantly public health risks associated with this dark trade.